Isolating the independent effects of hypoxia and hyperventilation-induced hypocapnia on cerebral haemodynamics and cognitive function - Friend, A. T.; Balanos, G. M.; Lucas, S. J. E. (Experimental Physiology, 2019)
Exposure to hyperventilation-induced hypocapnia causes cognitive impairment in both normoxia and hypoxia. In addition, supplementation of carbon dioxide during hypoxia alleviates the cognitive impairment and reverses hypocapnia-induced vasoconstriction of the cerebrovasculature. These data provide new evidence for the independent effect of hypocapnia on the cognitive impairment associated with hypoxia. Hypoxia, which is accompanied by hypocapnia at altitude, is associated with cognitive impairment. This study examined the independent effects of hypoxia and hypocapnia on cognitive function and assessed how changes in cerebral haemodynamics may underpin cognitive performance outcomes. Single reaction time (SRT), five-choice reaction time (CRT) and spatial working memory (SWM) tasks were completed in 20 participants at rest and after 1 h of isocapnic hypoxia (IH, end-tidal oxygen partial pressure () = 45 mmHg, end-tidal carbon dioxide partial pressure () clamped at normal) and poikilocapnic hypoxia (PH, = 45 mmHg, not clamped). A subgroup of 10 participants were also exposed to euoxic hypocapnia (EH, = 100 mmHg, clamped 8 mmHg below normal). Middle cerebral artery velocity (MCAv) and prefrontal cerebral haemodynamics were measured with transcranial Doppler and near infrared spectroscopy, respectively. IH did not affect SRT and CRT performance from rest (566 ± 50 and 594 ± 70 ms), whereas PH (721 ± 51 and 765 ± 48 ms) and EH (718 ± 55 and 755 ± 34 ms) slowed response times (P < 0.001 vs. IH). Performance on the SWM task was not altered by condition. MCAv increased during IH compared to PH (P < 0.05), which was unchanged from rest. EH caused a significant fall in MCAv and prefrontal cerebral oxygenation (P < 0.05 vs. baseline). MCAv was moderately correlated to cognitive performance (R2 = 0.266-0.289), whereas prefrontal cerebral tissue perfusion and saturation were not (P > 0.05). These findings reveal a role of hyperventilation-induced hypocapnia per se on the development of cognitive impairment during normoxic and hypoxic exposures.